A Human Rights Approach to Planning Families. (September 2019) - Hamity, Matthew; Dillard, Carter; Bexell, Sarah M.; Graff-Hughey, Catharina
We present reflections on the current normative model of family planning and provide a novel alternative model centred on children's rights. Over the last half-century, environmentalists, ecological economists, and child psychologists have raised key issues facing child rights: the threat of climate change and environmental degradation, the critical importance of childhood development, and growing economic inequality. As these challenges have become more widely recognised, organisations and governments have responded by investing in renewable energy, preschools, and availability of birth control. However, human population is expected to reach an alarming 11 billion or more in 2100, endangering nearly all life on Earth. Family planning interventions are the most effective way to reduce population growth and improve human well-being while simultaneously preventing ecological collapse. However, comprehensive attempts at articulating a human rights approach to family planning are lacking: here is our attempt.